131k views
0 votes
What is 3x^-2+7x^-1+2=0
?

User Nategood
by
5.4k points

1 Answer

4 votes

2x2-7x+3 = 0

Divide both sides of the equation by 2 to have 1 as the coefficient of the first term :

x2-(7/2)x+(3/2) = 0

Subtract 3/2 from both side of the equation :

x2-(7/2)x = -3/2

Now the clever bit: Take the coefficient of x , which is 7/2 , divide by two, giving 7/4 , and finally square it giving 49/16

Add 49/16 to both sides of the equation :

On the right hand side we have :

-3/2 + 49/16 The common denominator of the two fractions is 16 Adding (-24/16)+(49/16) gives 25/16

So adding to both sides we finally get :

x2-(7/2)x+(49/16) = 25/16

Adding 49/16 has completed the left hand side into a perfect square :

x2-(7/2)x+(49/16) =

(x-(7/4)) • (x-(7/4)) =

(x-(7/4))2

Things which are equal to the same thing are also equal to one another. Since

x2-(7/2)x+(49/16) = 25/16 and

x2-(7/2)x+(49/16) = (x-(7/4))2

then, according to the law of transitivity,

(x-(7/4))2 = 25/16

We'll refer to this Equation as Eq. #6.2.1

The Square Root Principle says that When two things are equal, their square roots are equal.

Note that the square root of

(x-(7/4))2 is

(x-(7/4))2/2 =

(x-(7/4))1 =

x-(7/4)

Now, applying the Square Root Principle to Eq. #6.2.1 we get:

x-(7/4) = √ 25/16

Add 7/4 to both sides to obtain:

x = 7/4 + √ 25/16

Since a square root has two values, one positive and the other negative

x2 - (7/2)x + (3/2) = 0

has two solutions:

x = 7/4 + √ 25/16

or

x = 7/4 - √ 25/16

Note that √ 25/16 can be written as

√ 25 / √ 16 which is 5 / 4

Solve Quadratic Equation using the Quadratic Formula

6.3 Solving 2x2-7x+3 = 0 by the Quadratic Formula .

According to the Quadratic Formula, x , the solution for Ax2+Bx+C = 0 , where A, B and C are numbers, often called coefficients, is given by :

- B ± √ B2-4AC

x = ————————

2A

In our case, A = 2

B = -7

C = 3

Accordingly, B2 - 4AC =

49 - 24 =

25

Applying the quadratic formula :

7 ± √ 25

x = —————

4

Can √ 25 be simplified ?

Yes! The prime factorization of 25 is

5•5

To be able to remove something from under the radical, there have to be 2 instances of it (because we are taking a square i.e. second root).

√ 25 = √ 5•5 =

± 5 • √ 1 =

± 5

So now we are looking at:

x = ( 7 ± 5) / 4

Two real solutions:

x =(7+√25)/4=(7+5)/4= 3.000

or:

x =(7-√25)/4=(7-5)/4= 0.500

Two solutions were found :

x = 1/2 = 0.500

x = 3

User Dmitry Sikorsky
by
5.2k points